Production information tracking system - Tioh, Keat Soon (2008)
Production Information Tracking System is a multipurpose system that consists of yield rejects report generation, tester frequency error retrieval, to generate emergency response template, visual graphical of rejected IC, and data retention issue management. Yield reject report is extracted from the data warehouse. Previously, it was hard for the engineer to analyze the history of tester frequency error. Engineer needs to utilize multi-system to generate the emergency response template. The system provides the solution for these problems. Besides that, operator can use the system to translate the number of the rejected pin of IC into graphical visual. Managing the data retention is a daunting task. By providing the lot number, the related information will be retrieved from database and exported to excel file. Lot protocol can also be searched easily. This system can be run on any platform and it does not require installation as long as the platform has a virtual machine.